Multiferroic Properties and Magnetoelectric Coupling of Fe‐Doped (Ba0.7Ca0.3)TiO3‐Ba(Zr0.2Ti0.8)O3 Ceramics. Issue 2 (12th December 2019) - Gong, Baolian; Huang, Fengzhen; Shao, Ye; Lei, Lin; Liu, Lin; Wang, Junjun; Yan, Shuo; Lu, Xiaomei; Zhu, Jinsong
Abstract : Fe‐doped (Ba0.7 Ca0.3 )TiO3 ‐Ba(Zr0.2 Ti0.8 )O3 (BCZT) ceramics are prepared by a conventional solid‐state reaction method, and their structure, multiferroic, and coupling properties are investigated. Ferromagnetism and magnetoelectric coupling are successfully realized by Fe 3+ doping. Meanwhile, Fe 3+ doping in BCZT results in a gradual transition from typical ferroelectrics to relaxor ferroelectrics or even quantum paraelectrics. In consequence, obvious magnetodielectric (MD) effect is observed only among the morphotropic phase boundary (MPB) temperature range. For (Ba1.7 Ca0.3 )(Zr0.2 Ti1.7 Fe0.1 )O6 ceramics, the coexistence of ferroelectricity and ferromagnetism along with a large MD effect is obtained below 200 K. Herein, the results highlight the role of MPB on the magnetoelectric coupling of ferroelectrics with a percolating of magnetic ions. Abstract : Ferromagnetism and magnetoelectric coupling are successfully realized by Fe 3+ doping in morphotropic phase boundary (Ba0.7 Ca0.3 )TiO3 ‐Ba(Zr0.2 Ti0.8 )O3 ceramics. The coexistence of ferroelectricity and ferromagnetism along with a large magnetodielectric effect is obtained in (Ba1.7 Ca0.3 )(Zr0.2 Ti1.7 Fe0.1 )O6 ceramics.